BMC ecology image competition 2018: the winning images - Alison L. Cuff; Ying Lou; Jiang Zhigang; Michel Baguette; Simon Blanchet; Jean Clobert; Luke M. Jacobus; Dominique Mazzi; Josef Settele (BMC Ecology, 2019)
Abstract The sixth BMC Ecology Image Competition received more than 145 photographs from talented ecologists around the world, showcasing the amazing biodiversity, natural beauty and biological interactions found in nature. In this editorial, we showcase the winning images, as selected by our guest judge, Professor Zhigang Jiang from the Institute of Zoology of the Chinese Academy of Sciences, with help from the journal’s editorial board. Enjoy!